Alkaline gastro-oesophageal reflux: dual probe pH monitoring. Issue 4 (October 1995) - Iftikhar, S Y; Ledingham, S; Evans, D F; Yusuf, S W; Steele, R J; Atkinson, M; Hardcastle, J D
Abstract : Although the aetiology of Barrett's oesophagus or columnar line oesophagus (CLO), remains unknown, bile reflux has been implicated as a factor in its pathogenesis. This study aimed to detect alkaline reflux in gastro-oesophageal reflux patients using dual probe pH monitoring. Thirty patients with histologically diagnosed CLO, 15 age and sex matched patients with oesophagitis (grade 1-3), and 15 healthy volunteers were studied by dual probe, 18 hour pH monitoring and analysis of the bile acid content of oesophageal refluxate. Total acid exposure and acid exposure in the upright and supine postures were greater in CLO subjects than in oesophagitis patients and controls. Furthermore, the number of reflux episodes lasting more than five minutes and the duration of the longest reflux episode were significantly greater in the CLO subjects than the oesophagitis and control subjects. Nine subjects with CLO and oesophagitis, however, were not identified as refluxers, although six had a bile acid concentration in their oesophageal aspirate higher than the 95th centile value of the controls. There was no correlation between the oesophageal pH and the bile acid contents of refluxate. It is concluded that dual probe pH monitoring is not useful in detecting alkaline refluxers. pH monitoring, although the only subjective test available to identify acid refluxers, is not a sufficiently sensitive test with which to define alkaline reflux.